Assessment of Safety, Efficacy and Predictability of a Trifocal Intraocular Lens: Doi: 10.36351/pjo.v39i2.1559 - Girgis, Marian; Osman, Amr; Eissa, Sherif A.; Anis, Mohamed; Barrada, Omar A.; Hasaballah, Mohamed (Pakistan Journal of Ophthalmology, 2023)
Purpose: To evaluate the performance and the visual outcomes of Acrysof PanOptix trifocal IOL in terms of safety, efficacy, predictability and assessment of the quality of vision after implantation as regards; contrast sensitivity and ocular aberrations. Study Design: Quasi experimental study. Place and Duration of Study: Dar el Ouyon hospital and Rowad Correction Center, Egypt, from September 2019 and January 2020. Methods: Forty eyes of twenty-one patients with senile cataract were included by convenient sampling. All eyes underwent phacoemulsification with IOL implantation. They were divided into two groups; group A included twenty eyes of eleven patients who were implanted AcrySof IQ PanOptix trifocal IOL Model TFNT00. Group B included twenty eyes of ten patients who were implanted monofocal AcrySof IOLs as a control group. A questionnaire was given to every patient after explaining to him\her the questions in Arabic, and clarifying the aim of evaluation. Results: Mean age was 56.6 ± 6.9 years in group A and 62.8 ± 7.1 years in group B, range 50 – 70 (P = 0.861). We found statistical significant difference between both groups with group A showing better post operative uncorrected distance, intermediate, near, and best corrected near visual acuity (P values were 0.001, 0.556, 0.001, 0.177, 0.001, 0.001 respectively). Group B showed statistically significant better post operative contrast sensitivity compared to group A. Conclusion: In this study, Acrysof PanOptix trifocal IOL showed excellent safety, efficacy, predictability and spectacle independence at all distances, However, contrast sensitivity was compromised in comparison to the monofocal group.